Mastering autodesk VIZ 2007 - Omura, George (Wiley Publishing, 2006)
Transform flat drawings and concepts into impressive 3D visualizations that will amaze your clients with the comprehensive instruction you'll find in Mastering Autodesk VIZ 2007. Written by VIZ experts, this book shows you how to get the most out of the latest version of Autodesk's powerful 3D design, modeling, and animation tool with an in-depth, tutorial-based approach grounded in real-world examples.